2014
DOI: 10.15381/rivep.v25i1.8468
|View full text |Cite
|
Sign up to set email alerts
|

SEROPREVALENCIA DE Neospora caninum EN BOVINOS LECHEROS DE CUATRO DISTRITOS DEL VALLE DEL MANTARO, JUNÍN.

Abstract: RESUMENEl objetivo del presente estudio fue determinar la frecuencia de Neospora caninum en vacas lecheras de la cuenca izquierda del Valle del Mantaro, Junín, Perú. Se analizaron 182 sueros de bovinos hembras provenientes de 15 establos lecheros de los distritos de Matahuasi, Concepción, 9 de Julio y Santa Rosa. Se utilizó la prueba de ELISA indirecta con un kit comercial para determinar anticuerpos contra N. caninum. Se encontró una seroprevalencia de 46.7 ± 7.2 % (85/182). Los distritos de Matahuasi y Santa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
2
0
2
Order By: Relevance
“…Seroprevalence of N. caninum in dairy cattle has been reported in different regions of Peru and described their association with aborts.. In the highlands, a seroprevalence of 46.7% was reported (GRANADOS et al, 2014), while in the Amazon rainforest it was 18.8% (PORTOCARRERO et al, 2015), in Lima Valley (Peru central coast) it was 29.6%-69.6% (GAMARRA et al, 2009;SILVA et al, 2002), and in our study it was 46.6%. Rivera reported 55% of aborted fetus with N. caninum presence in differents farms from Lima valley with different diagnostic test (RIVERA, 2001) and our study found 15% of aborted fetus.…”
Section: Discussionsupporting
confidence: 54%
“…Seroprevalence of N. caninum in dairy cattle has been reported in different regions of Peru and described their association with aborts.. In the highlands, a seroprevalence of 46.7% was reported (GRANADOS et al, 2014), while in the Amazon rainforest it was 18.8% (PORTOCARRERO et al, 2015), in Lima Valley (Peru central coast) it was 29.6%-69.6% (GAMARRA et al, 2009;SILVA et al, 2002), and in our study it was 46.6%. Rivera reported 55% of aborted fetus with N. caninum presence in differents farms from Lima valley with different diagnostic test (RIVERA, 2001) and our study found 15% of aborted fetus.…”
Section: Discussionsupporting
confidence: 54%
“…Thus, taking these parameters into account, in this work a logistic regression analysis was carried out, which gave us a result of species vs. primer association which was selective and specific with the numerical function and thus useful to discriminate between species of the same genus. Furthermore, the database was validated with the statistical program JMP ® Pro 13 and was built through visual analysis without using programs such as GelCompar II [ 35 ], PyElph [ 36 ], Quantity One [ 37 ] and Image Master [ 38 ], among others, which minimize the bias generated when obtaining data from polymorphic patterns; the data were also not normalized, as recommended in the literature [ 39 ]. The logistic regression model allowed the obtaining of ROC curves, which evaluated the sensitivity against the specificity of each primer for the different Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Estos datos los cuales fueron muestreados 87 animales concuerdan con otros estudios epidemiológicos pertenecientes a los Distritos de San Lorenzo, realizados sobre esta infección para otras zonas. Ñemby y Nueva Italia, del Departamento Central, con el objetivo de conocer la seroprevalencia de Esta enfermedad va diseminándose a los Neosporosis Bovina y su efecto sobre el intervalo establecimientos, los factores que podrían haber entre partos en el año 2018. facilitado la difusión de N. caninum serían; la permanencia de vacas seropositivas (transmisión vertical) dentro del hato, presencia de caninos que Finalizado el trabajo de campo y obtenido los conviven con los bovinos dentro de los establos y resultados de laboratorio, se realizó el análisis de los falta de medidas higiénicas sanitarias en las datos recabados, y el mismo arrojo los siguientes explotaciones lecheras (12). Un factor importante resultados: de un total de 87 muestras analizadas se sería también la no exigencia de pruebas que obtuvieron 36 muestras positivas que representa el certifiquen la seronegatividad de los animales 41,4% y 51 muestras resultaron negativas, incorporados al rebaño.…”
Section: De 31 L a B O R A T O R I O D E S E N A C S A E N T U B O S D Eunclassified